Evaluation of phosphorus, calcium, and magnesium content in commercially available foods formulated for healthy cats. (28th December 2019) - Summers, Stacie C.; Stockman, Jonathan; Larsen, Jennifer A.; Zhang, Lei; Rodriguez, Anais Sanchez
Abstract: Background: High dietary phosphorus (P) and low calcium‐to‐phosphorus ratio (Ca:P) are associated with kidney damage in cats. There are no established guidelines for dietary P maximum for cats. Objectives: To quantify crude protein, P, Ca, and magnesium (Mg) concentrations in cat foods and compare among food formats (dry, canned, raw), primary protein ingredients, protein concentrations (low, moderate, high), grain‐free versus grain‐containing foods, foods intended for adult maintenance versus all life stages, and cost. Samples: Eighty‐two commercial nonprescription cat foods. Methods: Descriptive study. Mineral concentrations were measured using inductively coupled argon plasma‐optical emission spectroscopy. Crude protein was measured using the Dumas nitrogen combustion method. Mineral and crude protein concentrations were compared among food categories. Results: Twenty‐seven foods contained ≥3.6 g P/1000 kcal metabolizable energy (ME), of which 7 exceeded 4.8 g/1000 kcal ME. Thirteen foods had low Ca:P ratio (≤1.0). The low‐protein diet group had no products ≥3.6 g P/1000 kcal ME, which was significantly different compared to the high‐protein diet group (52% of products had ≥3.6 g P/1000 kcal ME; P = .01). No significant differences in P content and Ca:P ratio were found among other diet categories. Canned foods had significantly lower Mg compared to dry ( P < .001) and raw ( P = .007) foods. Declared minimum P and Ca were significantly lower than analyzed concentrations ( P = .0005 and P = .003, respectively). Conclusions and Clinical Importance: The high number of foods with high P and low Ca suggest that pet food regulatory reform should be considered.